2020
DOI: 10.3390/microorganisms8091413
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Newly Isolated Akkermansia muciniphila Strains from the Human Gut on Obesity and Metabolic Dysregulation

Abstract: The identification of new probiotics with anti-obesity properties has attracted considerable interest. In the present study, the anti-obesity activities of Akkermansia muciniphila (A. muciniphila) strains isolated from human stool samples and their relationship with the gut microbiota were evaluated using a high fat-diet (HFD)-fed mice model. Three strains of A. muciniphila were chosen from 27 isolates selected based on their anti-lipogenic activity in 3T3-L1 cells. The anti-lipogenic, anti-adipogenic and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 87 publications
9
53
0
3
Order By: Relevance
“…It is recognized that A. muciniphila could play a crucial role on the obesity parameters in human and different mice models, such as reduced body weight, fat mass, hip circumfer-ence, caloric intake, mesenteric fat weight, subcutaneous fat weight, epididymal fat weight, total fat and energy efficiency [29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is recognized that A. muciniphila could play a crucial role on the obesity parameters in human and different mice models, such as reduced body weight, fat mass, hip circumfer-ence, caloric intake, mesenteric fat weight, subcutaneous fat weight, epididymal fat weight, total fat and energy efficiency [29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of A. muciniphila on obesity and glucose metabolism, it was thought to be involved in inflammation modulation. The results of Yang et al [29] showed that in the HFD group, TNF-a, IL-6, MCP-1, TLR2 and TLR4 colonic mRNA levels were significantly higher than in the normal group. Conversely, the colonic expression of the IL-10 gene was significantly lower.…”
Section: A Muciniphila In Improvement Of Anti-inflammatory Effectsmentioning
confidence: 94%
See 3 more Smart Citations